Compositional analysis of obsidian artifacts from the Templo Mayor of Tenochtitlan, capital of the Mexica (Aztec) Empire - Diego Matadamas-Gomora; Jason Nesbitt; Rodolfo Aguilar Tapia; Leonardo López Luján; Julia Sjödahl; Tatsuya Murakami; Alejandro Pastrana (Proceedings of the National Academy of Sciences, 2025)
This study presents the results of geochemical compositional analysis through portable X-ray fluorescence of 788 artifacts from the Templo Mayor in Mexico City. The results reveal that the Mexica (Aztecs) preferred green obsidian from Sierra de Pachuca. However, a diachronic analysis (c. 1375-1520 CE) demonstrated that they continuously consumed obsidian from seven additional sources with some temporal variations related to the sociopolitical transformations of the empire. In the early phases, obsidian from Tulancingo, El Paraíso, and Zacualtipán is more common. After the consolidation of the Mexica Empire c.1430 CE, the patterns shifted to obsidian from Otumba, Paredón, and Ucareo. The study of artifacts from ritual and nonritual contexts demonstrates that most inhabitants used obsidian from multiple regions in the form of blades and flakes, probably acquired in local markets. Conversely, the elites and ritual specialists clearly preferred green obsidian from Pachuca to elaborate ritual objects due to its unique color and symbolic value. Ritual objects may arrive directly at the sacred precinct from the workshops outside the city, such as those found in Otumba and Pachuca. This study highlights the importance of analyzing large samples that combine ritual and nonritual artifacts, as well as objects from different phases, to explore temporal and social patterns of obsidian consumption among Pre-Hispanic societies.